2005
DOI: 10.2460/ajvr.2005.66.589
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between hoof-acceleration patterns of galloping horses and dynamic properties of the track

Abstract: The inverse relationship between track rebound rate and negative acceleration peaks for all hooves reflects the most important dynamic property of a track. Any factor that reduces negative acceleration of the hooves will increase stride efficiency by allowing smoother transition from retardation to propulsion and therefore may be important in determining the safety of racing surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 15 publications
10
68
0
5
Order By: Relevance
“…Rebound rate, measured with an earlier version of the TTD [10], was thought to be the most useful dynamic property of the track, as it was most consistently related to hoof accelerations measured by instrumented horses [12]. The positive relationship between TTD rebound rate and peak hoof acceleration during the braking-propulsion transition indicates that low rebound rates would result in efficient strides and low limb stresses [12].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Rebound rate, measured with an earlier version of the TTD [10], was thought to be the most useful dynamic property of the track, as it was most consistently related to hoof accelerations measured by instrumented horses [12]. The positive relationship between TTD rebound rate and peak hoof acceleration during the braking-propulsion transition indicates that low rebound rates would result in efficient strides and low limb stresses [12].…”
Section: Discussionmentioning
confidence: 97%
“…The positive relationship between TTD rebound rate and peak hoof acceleration during the braking-propulsion transition indicates that low rebound rates would result in efficient strides and low limb stresses [12]. For the current study, the TTD was modified for multi-axis measurements and better simulation of horse hoof impact for a more appropriate assessment of surface properties [13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A small minority of these studies (7), eschewed applications to metabolism and instead remained within the traditional realm of evaluating performance: running in racehorses [113][114][115][116][117], swimming in sea snakes [118], and flight in Procellariform sea birds [119]. The remaining 90% of articles focused on energy efficiency during locomotion for travel or foraging [31,35,94,[120][121][122][123][124].…”
Section: Survey Of Questions Currently Served By Accelerometry: Biomementioning
confidence: 99%
“…Therefore, differences in the sport-functional properties of riding surfaces can be expected. Some previous studies have shown the possibility to illustrate the influence of the surface on the stress on the horse's limbs by acceleration measurements on the horse's hooves [2][3][4][5][6][7][8]. However, a high variability between and within horses has been found in acceleration data [6].…”
Section: Introductionmentioning
confidence: 95%